PENGGUNAAN MEDIA KARTU ABJAD BERGAMBAR TERHADAP PENING-KATAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SEKOLAH DASAR - Annisa Rukmana Dalima; Eka Sari Pera Ayu; Jubaidah; Maulida Rahmah; Ulfina; Maimunah; Ahmad Suriansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low early reading skills of second-grade students at SDN Sungai Miai 4 Banjarmasin, which was caused by conventional teaching methods and minimal use of engaging learning media. The purpose of this study was to determine the effect of using picture alphabet cards on improving the early reading skills of elementary school students. This study used a descriptive qualitative method with 17 second-grade students and one Indonesian language teacher as subjects. Data were collected through observation, documentation, and reading tests before and after the application of illustrated alphabet cards. The results showed that the use of picture alphabet cards improved students' early reading skills in terms of letter recognition, word pronunciation, reading comprehension, and the use of punctuation and intonation. In addition, this media also had a positive impact on students' motivation and confidence in reading, as well as creating a more interactive, enjoyable, and participatory learning atmosphere. Illustrated alphabet cards have been proven to be effective as visual aids that are appropriate for the cognitive development stage of elementary school children, as explained in the theories of Piaget, Bruner, and Vygotsky, which emphasize the importance of visual-based learning and scaffolding in the zone of proximal development. Thus, the use of illustrated alphabet cards can be used as an innovative alternative to improve students' basic literacy skills while strengthening the quality of the Indonesian language learning process in elementary schools.